Upaya Pencegahan Penularan HIV Ibu ODHA ke Anak di Kota Makassar - Fatmah Afrianty Gobel; Fairus Prihatin Idris; Fitriyani Fitriyani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
The risk of infants contracting HIV can be reduced by 2% through the Prevention of Mother-to-Child Transmission (PMTCT) program. This study aims to analyze efforts to prevent mother-to-child transmission of HIV in Makassar City. This type of research was quasi qualitative, which emphasizes descriptive qualitative. Respondents were recruited using snowball sampling technique. The validity of the data was carried out by triangulating sources from interviews with HIV-positive mothers as the main informants and midwives and people with HIV-AIDS peer companion as key informants. Data were analyzed by processing transcripts of interview results, sorting words or sentences to make it easier to analyze information. The results of the analysis are presented in a narrative manner according to the patterns found. It is recommended that health workers improve their ability to conduct counseling for mothers and their husbands. Keywords: HIV-AIDS; mother-to-child transmission; prevention; obedience ABSTRAK Risiko bayi tertular HIV bisa ditekan hingga 2% melalui program Prevention of Mother-to-Child Transmission (PMTCT). Penelitian ini bertujuan untuk menganalisis upaya pencegahan penularan HIV dari ibu ke anak di Kota Makassar. Jenis penelitian ini adalah kuasi kualitatif, yang menekankan pada deskriptif kualitatif. Responden direkrut dengan teknik snowball sampling. Keabsahan data dilakukan dengan triangulasi sumber dari wawancara dengan ibu dengan HIV positif sebagai informan utama dan bidan serta orang dengan HIV-AIDS pendamping sebaya sebagai informan kunci. Data dianalisis dengan mengolah transkrip hasil wawancara, memilah kata atau kalimat untuk memudahkan menganalisis informasi. Hasil analisis disajikan secara naratif sesuai dengan pola yang ditemukan. Disarankan kepada petugas kesehatan agar lebih meningkatkan kemampuan dalam melakukan konseling bagi ibu dan suaminya. Kata kunci: HIV-AIDS; penularan dari ibu ke anak; pencegahan; kepatuhan